Comparison of Pre-Treatment vs. Post-Treatment Retinal Vessel Density in Children with Amblyopia. Issue 3 (2nd July 2020) - Gunzenhauser, Robert C.; Tsui, Irena; Velez, Federico G.; Fung, Simon SM; Demer, Joseph L.; Suh, Soh Y.; Sarraf, David; Pineles, Stacy L.
ABSTRACT: Background: Prior studies have reported a lower retinal vessel density (RVD) in amblyopic vs. non-amblyopic eyes. No studies have shown if amblyopic eye RVD changes following patching therapy. We assessed for RVD differences between pre-treatment vs. post-treatment amblyopic eyes. Methods: Participants were included if they were <10 years old with unilateral amblyopia. All subjects were required to visit the pediatric eye clinic for examination. Exclusion criteria included: deprivation amblyopia, bilateral amblyopia, nystagmus, media opacity, intraocular inflammation, or any retinal disease. All participants underwent optical coherence tomography angiography (OCTA) before and after refraction and patching treatment. Outcomes included superficial (SCP) and deep (DCP) capillary plexus RVD. Results: 12 patients (12 amblyopic eyes) were included. Mean (SD) age, gestational age (GA), birth weight (BW), and follow-up time were: 6.5 (1.7) years, 39.4 weeks (1.4 w), 3271 g (262 g), and 114 days (46d), respectively. There was a significant increase in the RVD of the DCP in 3 × 3-mm scans after treatment, specifically in the whole image (52.6 ± 5.75 vs 56.5 ± 2.48%, p = .046) and superior hemisphere regions (52.47 ± 6.17 vs 56.73 ± 2.27%, p = .048). Conclusions: Amblyopic eye RVD potentially increases after amblyopia treatment in specific regions of the retina. Further research is required to refine this clinical parameter.